2014
DOI: 10.2514/1.c032470
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Tracking of Blind Sealant Paths in Friction Stir Lap Joining

Abstract: An automatic joint-tracking technique that employs an extremum-seeking controller is evaluated as a method for automatically tracking sealant paths that have been applied in dissimilar friction stir lap joints of 2024 and 7075 aluminum alloys. Sealants are commonly used to prevent the ingress of corrosion at the faying surfaces of lap joints, and in this study, an attempt is made to exploit sealant presence to reduce necessary robotic path planning procedures. Controller parameters are tuned, and baseline trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The need to combine surface treatments, sealants and joining technologies is a continuous challenge in the manufacturing of structures such as reinforced fuselage panels. In fact, several authors investigated the feasibility of FSW and its derivatives such as refill friction stir spot welding (RFSSW) for joining surface-treated aluminium alloys in the overlap configuration using sealants [13][14][15][16][17]. These studies showed a promising potential of FSW technologies to join surface-treated aluminium alloys using sealants in appropriate welding conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The need to combine surface treatments, sealants and joining technologies is a continuous challenge in the manufacturing of structures such as reinforced fuselage panels. In fact, several authors investigated the feasibility of FSW and its derivatives such as refill friction stir spot welding (RFSSW) for joining surface-treated aluminium alloys in the overlap configuration using sealants [13][14][15][16][17]. These studies showed a promising potential of FSW technologies to join surface-treated aluminium alloys using sealants in appropriate welding conditions.…”
Section: Introductionmentioning
confidence: 99%
“…From a general manufacturing of aircraft structures point of view, it is necessary to investigate the feasibility to combine surface treatments, sealants, and joining technologies. Several authors investigated the feasibility of FSW and its derivatives such as refill friction stir welding (RFSSW) for joining surface-treated aluminium alloys in the overlap configuration using sealants [28][29][30][31][32]. These studies demonstrated a good potential of FSW technologies to weld surface-treated aluminium alloys using sealants with appropriate welding conditions and materials.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, several researchers have made efforts around the detection technologies to detect this special joint. A control system for automatic seam tracking for T-joint FSW based on weaving was presented [17,18], in the proposed technology, the tool weaves back and forth perpendicular to the joint line during welding in order to discover the position of maximal axial force, which is shown to be the center of the weld. The information of deviation status is acquired by the metallic vapor plume, which is influenced by instability or rupture of keyhole while the torch deviates from the weld seam [19].…”
Section: Introductionmentioning
confidence: 99%